Ionization-induced tautomerization in cytosine and effect of solvation - Das, Tamal; Ghosh, Debashree (Journal of Physical Chemistry A, 2014)
The recent observation of excitation-induced tautomerization in gas-phase cytosine motivated us to investigate the possibility of facile tautomerization in ionized cytosine and the effect of solvation on the tautomerization barriers. The tautomerization mechanisms were characterized at the density functional theory (DFT)omega B97X-D and coupled-cluster singles and doubles (CCSD) levels of theory. Vertical and adiabatic ionization energies (VIEs and AIEs, respectively) of the tautomers of cytosine and the microsolvated species were calculated with the equation-of-motion ionization-potential coupled-cluster (EOM-IP-CCSD) method. We observed that, in microsolvated cytosine, the solvatochromic shifts of the VIEs can be both blue- and red-shifted depending on the tautomers. This is explained by the analysis of the charge dipole interactions between the cytosine and water molecules. We noticed that, upon ionization, gas-phase tautomerization barriers are reduced by 0-4 kcal/mol, whereas microsolvated (with one water) tautomerization barriers are reduced by 4-5 kcal/mol. We also investigated the tautomerization process in solvation using a continuum model with one active water molecule in the quantum mechanical region. We noticed that, even though bulk solvation has a significant effect on ionization energies, its effect on the ionization-induced tautomerization barrier is minimal.

Feasibility of ionization-mediated pathway for ultraviolet-induced melanin damage - Mandal, Mukunda; Das, Tamal; Grewal, Baljinder K.; Ghosh, Debashree (Journal of Physical Chemistry B, 2015)
Melanin is the pigment found in human skin that is responsible for both photoprotection and photodamage. Recently there have been reports that greater photodamage of DNA occurs when cells containing melanin are irradiated with ultraviolet (UV) radiation, thus suggesting that the photoproducts of melanin cause DNA damage. Photoionization processes have also been implicated in the photodegradation of melanin. However, not much is known about the oxidation potential of melanin and its monomers. In this work we calculate the ionization energies of monomers, dimers, and few oligomers of eumelanin to estimate the threshold energy required for the ionization of eumelanin. We find that this threshold is within the UV-B region for eumelanin. We also look at the charge and spin distributions of the various ionized states of the monomers that are formed to understand which of the ionization channels might favor monomerization from a covalent dimer.

Exploration of the diastereoselectivity in an unusual Grignard reaction and its application towards the synthesis of styryl lactones 7-epi-(+)-goniodiol and 8-epi-(-)-goniodiol - Chavan, Subhash P.; Khatod, Harshali S.; Das, Tamal; Vanka, Kumar (RSC Advances, 2016)
An unusual diastereoselective Grignard reaction is explored, where the Grignard reagents are derived from 1,n-dihaloalkanes. A steric bias due to the presence of a quaternary centre adjacent to the acetonide ester at the benzylic position is responsible for the formation of an intramolecularly reduced product in almost quantitative yield. This steric hindrance is responsible for the diastereoselectivity observed with a variety of aromatic as well as aliphatic esters. The unusual Grignard reaction furnishes long chain secondary alcohols possessing a terminal olefin, which are synthetically important intermediates. As an application of this method, the diastereoselective synthesis of styryl lactones viz. 7-epi-(+)-goniodiol (29) and 8-epi(-)-goniodiol (30) has been achieved.

Facile access to a Ge(II) dication stabilized by isocyanides - Swamy, V. S. V. S. N.; Yadav, Sandeep; Pal, Shiv; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2016)
Herein, we introduce isocyanide as a ligand in main group chemistry and describe the facile isolation of a Ge(II) dication. The reaction of 2,6-dimethylphenylisocyanide with GeCl2 leads to the formation of a Ge(II) dication with two [GeCl3](-) molecules as counter anions. The dicationic Ge(II) center is bound to four isocyanide ligands and also holds a lone pair of electrons. DFT calculations reveal that the dication is stabilized only by sigma-donation from the four isocyanide ligands. Natural population analysis gives a charge of +0.74 on the Ge(II) center, indicating that the positive charge is shared by the isocyanide substituents.

Intramolecular dehydrogenative coupling of 2,3-diaryl acrylic compounds: access to substituted phenanthrenes - Gupta, Vijay; Rao, V. U. Bhaskara; Das, Tamal; Vanka, Kumar; Singh, Ravi P. (Journal of Organic Chemistry, 2016)
A simple, facile, and environmentally benign intramolecular dehydrogenative coupling of various 1,2-diarylethylenes for the synthesis of phenanthrenes in excellent yield has been described. This new methodology uses ceric ammonium nitrate (CAN) as a promoter at room temperature and has been extended to intermolecular synthesis of biaryl compounds. The electron transfer from methoxyarene to cerium leads to cationic radical formation, which further proceeds to intramolecular coupling. Preliminary mechanistic investigation by EPR spectroscopy and density functional theory calculation suggested a similar view.

DBU-mediated diastereoselective aldol-type cyanomethylation of isatins - Rao, V. U. Bhaskara; Kumar, Krishna; Das, Tamal; Vanka, Kumar (Journal of Organic Chemistry, 2017)
An efficient, metal-free approach to 3-substituted 3-hydroxybxindole by DBU-mediated highly diastereoselective addition of aryl acetonitrile to N-protected isatin under mild conditions has been developed. The reaction proceeds smoothly to produce respective cyanomethylated adducts in good yield and excellent diastereoselectivity. Further transformation of the cyanide group allowed the synthesis of an advance intermediate of corresponding (+/-) CPC analogue. The mechanistic insight :toward the aldol-type cyanomethylation, of N-tritylisatin with benzyl cyanide was obtained by DFT calculations.

Metal free mild and selective aldehyde cyanosilylation by a neutral penta-coordinate silicon compound - Swamy, V. S. V. S. N.; Bisai, Milan Kumar; Das, Tamal; Sen, Sakya S. (Chemical Communications, 2017)
This study demonstrates the preparation and structural characterization of a Si(IV) hydride (PhC(NtBu)(2)SiH(CH3)Cl) (1) and its use as a catalyst for the cyanosilylation of a variety of aldehydes. Compound 1 represents the first neutral penta-coordinate silicon(IV) species that catalyzes cyanosilylation of aldehydes under mild conditions.

Transition metal free catalytic hydroboration of aldehydes and aldimines by amidinato silane - Bisai, Milan; Pahar, Sanjukta; Das, Tamal; Sen, Sakya S. (Dalton Transactions, 2017)
The transition metal free catalytic hydroboration of aldehydes and ketones is very limited and has not been reported with a well-defined silicon(iv) compound. Therefore, we chose to evaluate the previously reported silicon(iv) hydride [PhC(NtBu)2SiHCl2], (1) as a single component catalyst and found that it catalyzes the reductive hydroboration of a range of aldehydes with pinacolborane (HBpin) under ambient conditions. In addition, compound 1 can catalyze imine hydroboration. DFT calculation was carried out to understand the mechanism.

Easily accessible lithium compound catalyzed mild and facile hydroboration and cyanosilylation of aldehydes and ketones - Bisai, Milan; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2018)
Simple and readily accessible lithium compounds such as 2,6-ditertbutyl phenolate lithium (1a), 1,1' dilithioferrocene (1b) and nacnac lithium (1c) are found to be efficient single site catalysts for hydroboration of...

Mechano-responsive room temperature luminescence variations of boron conjugated pyrene in air - Wakchaure, Vivek C.; Ranjeesh, Kayaramkodath C.; Goudappagouda; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh; Babu, Sukumaran S. (Chemical Communications, 2018)
Stimuli responsive tunable luminescence is a promising field of research. Even though mechanofluorescence is widely studied, mechanophosphorescence remains unexplored. Here we report the mechano-driven fluorescence and phosphorescence variations of a pyrene tetraboronic ester derivative. The fluorochromic and room temperature phosphorescence features are supported by theoretical studies and single crystal analysis. The mechanically ground fluorescence active but phosphorescence inactive pyrene tetraboronic ester exhibits room temperature phosphorescence in air withmechanical force. The efficient intermolecular electronic coupling in the dimer formed upon scratching enables a good communication between singlet and triplet states, hence resulting in room temperature mechanophosphorescence.

Twelve-armed hexaphenylbenzene-based giant supramolecular framework for entrapping guest molecules - Madhu, Suresh; Gonnade, Rajesh G.; Das, Tamal; Vanka, Kumar; Sanjayan, Gangadhar J. (ChemPlusChem, 2018)
Host-guest chemistry is a functional model in supramolecular chemistry for understanding specific process occurring in biological systems. Herein, we describe a rationally designed giant multiarmed hexaphenylbenzene (HPB)-based supramolecular frameworks which encapsulate a variety of guest molecules in the voids of their crystal lattice through the cooperative interplay of multivalency, noncovalent forces and backbone rigidity. In this connection, pseudo-axially substituted twelve-armed hexaphenylbenzene was synthesized and its molecular entrapping nature was studied by varying number of H-bond donor-acceptor sites in the arms. The per-methyl esterified HPB acted as a cavitand to include nonpolar and polar aprotic guests in its crystal structure via C-H center dot center dot center dot pi, C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions. The corresponding amidated HPB showed unprecedented inclusion of ammonia and segregation of the guest molecules according to their polarity in the lattice. Furthermore, this molecular entrapping system has been used to obtain the crystal structure of a hitherto unproven 2-azaallenium intermediate, which had been proposed to be involved in aminomethylation of activated arenes.

Boron-conjugated pyrenes as fluorescence-based molecular probes and security markers - Wakchaure, Vivek Chandrakant; Das, Tamal; Babu, Sukumaran Santhosh (ChemPlusChem, 2019)
Boron-embedded aromatic hydrocarbons are a class of molecules known for their distinct electronic and/or optoelectronic properties and are thus suitable for many potential applications. Among those, boronic ester and acid containing molecules have been widely used for sensing and molecular recognition applications, respectively. We compared the sensing and molecular recognition properties of two boron-containing pyrene derivatives for fluoride and glucose sensing applications. The presence of four boronate ester groups enabled fluoride ion sensing at the mu M level. The boronic acid derivative is very selective towards glucose compared to other saccharides. Furthermore, we used the mechano-responsive fluorescence changes and self-assembly of these derivatives, respectively, for fluorescence-based inkless and ink (water)-based writing in invisible security labeling applications.
Keywords: boron; carbohydrates; mechanoluminescence; pyrene; sensors

Insights into the origin of life: did it begin from HCN and H2O? - Das, Tamal; Ghule, Siddharth; Vanka, Kumar (Acs Central Science, 2019)
The seminal Urey-Miller experiments showed that molecules crucial to life such as HCN could have formed in the reducing atmosphere of the Hadean Earth and then dissolved in the oceans. Subsequent proponents of the "RNA World" hypothesis have shown aqueous HCN to be the starting point for the formation of the precursors of RNA and proteins. However, the conditions of early Earth suggest that aqueous HCN would have had to react under a significant number of constraints. Therefore, given the limiting conditions, could RNA and protein precursors still have formed from aqueous HCN? If so, what mechanistic routes would have been followed? The current computational study, with the aid of the ab initio nanoreactor (AINR), a powerful new tool in computational chemistry, addresses these crucial questions. Gratifyingly, not only do the results from the AINR approach show that aqueous HCN could indeed have been the source of RNA and protein precursors, but they also indicate that just the interaction of HCN with water would have sufficed to begin a series of reactions leading to the precursors. The current work therefore provides important missing links in the story of prebiotic chemistry and charts the road from aqueous HCN to the precursors of RNA and proteins.

Lithium compounds as single site catalysts for hydroboration of alkenes and alkynes - Bisai, Milan Kumar; Yadav, Sandeep; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2019)
The hydroboration of alkenes and alkynes using easily accessible lithium compounds [2,6-di-tert-butyl phenolatelithium (1a) and 1,1 ` dilithioferrocene (1b)] has been achieved with good yields, high functional group tolerance and excellent chemoselectivity. Deuterium-labeling experiments confirm the cis-addition of pinacolborane. The methodology has been further extended to myrcene, which undergoes selective 4,3-hydroboration. DFT calculations provide insights into the mechanism.

Phosphite-Catalyzed C-H allylation of azaarenes via an enantioselective [2,3]-Aza-wittig rearrangement - Motaleb, Abdul; Rani, Soniya; Das, Tamal; Gonnade, Rajesh G.; Maity, Pradip (Angewandte Chemie-International Edition, 2019)
A phosphite-mediated [2,3]-aza-Wittig rearrangement has been developed for the regio- and enantioselective allylic alkylation of six-membered heteroaromatic compounds (azaarenes). The nucleophilic phosphite adducts of N-allyl salts undergo a stereoselective base-mediated aza-Wittig rearrangement and dissociation of the chiral phosphite for overall C-H functionalization of azaarenes. This method provides efficient access to tertiary and quaternary chiral centers in isoquinoline, quinoline, and pyridine systems, tolerating a broad variety of substituents on both the allyl part and azaarenes. Catalysis with chiral phosphites is also demonstrated with synthetically useful yields and enantioselectivities.

Synthesis and reactivity of a hypersilylsilylene - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Inorganic chemistry, 2019)
Stabilization of an amidinatosilylene with a bulky tris(trimethylsilyl)silyl substituent was realized with the preparation of PhC(NtBu)(2)Si{Si(SiMe3)(3)} (1) from PhC(NtBu)(2)SiHCl2 with K{Si(SiMe3)(3)} in more than 90% yield. The highly deshielded Si-29 NMR resonance (delta = 76.91 ppm) can be attributed to the absence of a pi-donating substituent. The molecular structure of 1 shows a trigonal-planar geometry around the Si-II center with a Si-II-Si-IV bond length of 2.4339(13) angstrom. A series of reactions of 1 with Me3NO, S, Se, and Te were performed. While siloxane derivatives (2 and 3) are obtained from reactions with Me3NO, silachalcogenones (4-6) are formed with other chalcogens. The presence of Si=E (E = S, Se, and Te) bonds in 4-6 have been confirmed by single crystal X-ray studies. Silaoxirane (7) formation was observed when 1 was treated with acetone, demonstrating the importance of the tris(trimethylsilyl)silyl group to kinetically and thermodynamically protect the silaoxirane derivative with less bulky substituents on the C atom.

Access to diverse germylenes and a six-membered dialane with a flexible beta-diketiminate - Pahar, Sanjukta; Swamy, V. S. V. S. N.; Das, Tamal; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2020)
A nacnac-based tridentate ligand containing a picolyl group (L) was employed to isolate chlorogermylene (1). The reaction of1with another equivalent of GeCl2 center dot dioxane surprisingly gave pyridylpyrrolide-based chlorogermylene (2)viaC-N bond cleavage and C-C coupling, while with AlCl3, it afforded a transmetalated product,4. The reaction of L with AlH3 center dot NMe2Et led to an unusual cyclohexane type six-membered dialane heterocycle (5).

Dual mode selective detection and differentiation of TNT from other nitroaromatic compounds - Patil, Goudappagouda; Dongre, Sangram D.; Das, Tamal; Babu, Sukumaran Santhosh (Journal of Materials Chemistry A, 2020)
Selective detection of explosives, especially TNT, is a highly desirable area of research and various explosives detection devices including fluorescent sensors are already in place. However, multi-mode sensors will be more useful and reliable than conventional fluorescent ``Turn Off'' sensors. One of the challenges is the development of selective sensors to prevent illegal transport of commonly used explosive TNT through on-the-spot analysis. In this context, we report a fluorescent polymer-based selective detection of TNT using both fluorometric and colorimetric signals. In addition, colorimetric differentiation of TNT from other nitroaromatic compounds is made possible by complexing with various amines. Even though many other sensors are available for TNT, the current demonstration is unique in terms of selectivity, sensitivity, reliability, portability, and rapidity of results. The as-developed explosive detection kit can be useful in both civilian and military operations to trace the illegal transport of TNT as well as for post-explosion analysis.

Transmetallation vs adduct: diverse reactivity of N,O-ketiminato germylene with [Cp*MCl2](2) (M = Rh or Ir; Cp* = eta(5)-C5Me5) and MCl5 (M = Nb and Ta) - Raghavendra, Beesam; Bakthavachalam, K.; Das, Tamal; Roisnel, Thierry; Sen, Sakya S.; Vanka, Kumar; Ghosh, Sundargopal (Journal of Organometallic Chemistry, 2020)
The reactions of the germylenes, [(Dipp)NCMeCHCORGeCl] (1a: R = Me, 1b: R = Ph) with [Ir2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] led to the formation of the adducts [(Dipp)NCMeCHCORGeClIrCl2Cp*] (3a: R = Me and 3b: R = Ph). On the other hand, [Rh2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] does not react with the germylenes (1a and 1b). When the reactions of 1a and 1b are carried out with [Cp*TaCl4], the reaction led to decomposition. The reaction of 1a or 1b with TaCl5 yielded the transmetallated products [(Dipp)NCMeCHCORTaCl4] (4a: R = Me, 4b: R = Ph) with the extrusion of GeCl2. Our theoretical studies show that for, the insertion of TaCl5 to 1a and the formation of 4a with concomitant elimination of GeCl2 is energetically favourable. Extrusion of SnCl2 is also observed when the corresponding stannylene, [(Dipp)NCMeCHCOMeSnCl] was reacted with TaCl5. All these compounds have been characterized by H-1 and C-13 NMR spectroscopy, elemental analysis and the constitution of compounds 1b, 3b, and 4a were confirmed by single-crystal X-ray crystallography. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Adduct formation; Germylenes; Iridium; Ketoiminate; Tantalum; Transmetallation

Diverse reactivity of carbenes and silylenes towards fluoropyridines - Kundu, Gargi; Ajithkumar, V. S.; Bisai, Milan Kumar; Tothadi, Srinu; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2- as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C-F bond activation leaving C-H bonds intact (5b). The reaction of SIDipp with C5F5N in the presence of BF3 afforded the ring cleavage product (3). Analogous reactions with silylene led to oxidative addition at the Si(II) center.

Excimer to exciplex transition through realization of donor-acceptor interactions in luminescent solvent-free liquids - Wakchaure, Vivek Chandrakant; Goudappagouda; Das, Tamal; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Nanoscale, 2021)
Luminescent solvent-free organic liquids are known for their enhanced quantum yield, color tunability, and availability of a matrix for other dopants to generate hybrid luminescent materials with improved features for newer applications. Herein, we report a donor-acceptor based luminescent ``exciplex liquid'' by utilizing the slightly different electron affinity of the acceptor molecules. A red-shifted broad exciplex emission exhibited by the donor-acceptor pair even at a lower concentration of the acceptor (0.001 equiv.) indicates high efficiency in the solvent-free state. A detailed NMR study revealed weak intermolecular interactions between the donor and acceptor in the solvent-free matrix that stabilizes the exciplex liquid. The failure of structurally similar solid counterparts to form an exciplex confirms the advantage of the available supportive liquid matrix. Besides, the luminescent exciplex liquid is found efficient in sensing application, which is unachievable by either the individual liquids or their solid counterparts. Here, a transition of a donor-acceptor pair from a solid to solvent-free liquid results in a new hybrid liquid that can be an alternative for solid sensor materials.

Insights into chemical reactions at the beginning of the universe: from HeH+ to H-3 (+) - Dash, Soumya Ranjan; Das, Tamal; Vanka, Kumar (Frontiers in Chemistry, 2021)
At the dawn of the Universe, the ions of the light elements produced in the Big Bang nucleosynthesis recombined with each other. In our present study, we have tried to mimic the conditions in the early Universe to show how the recombination process would have led to the formation of the first ever formed diatomic species of the Universe: HeH+, as well as the subsequent processes that would have led to the formation of the simplest triatomic species: H-3 (+). We have also studied some special cases: higher positive charge with fewer number of hydrogen atoms in a dense atmosphere, and the formation of unusual and interesting linear, dicationic He chains beginning from light elements He and H in a positively charged atmosphere. For all the simulations, the ab initio nanoreactor (AINR) dynamics method has been employed.
Keywords: ab initio molecular dynamics; ab initio nanoreactor; Density functional theory; origin of molecules in the universe; the earliest lewis acid

Lithium compound catalyzed deoxygenative hydroboration of primary, secondary and tertiary amides - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Dalton Transactions, 2021)
A selective and efficient route for the deoxygenative reduction of primary to tertiary amides to corresponding amines has been achieved with pinacolborane (HBpin) using simple and readily accessible 2,6-di-tert-butyl phenolate lithium center dot THF (1a) as a catalyst. Both experimental and DFT studies provide mechanistic insight.

Readily available lithium compounds as catalysts for the hydroboration of carbodiimides and esters - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Journal of Organometallic Chemistry, 2021)
Selective and efficient hydroboration of esters and carbodiimides to alcohols and amines by two welldefined and readily accessible lithium complexes, 2,6-di-tert-butyl phenolate lithium (1a ) and 1,1'-dilithioferrocene (1b ) are described. A range of aliphatic, aromatic, and cyclic esters with various functional groups were selectively converted into the corresponding boronate esters. Similarly, the single hydroboration of carbodiimides with aliphatic and aromatic substituents on the nitrogen atoms was studied. A possible mechanistic pathway of the hydroboration of carbodiimides with HBpin has been proposed using NMR studies and DFT calculations. These reactions are convenient alternatives to stoichiometric hydride reduction or hydrogenation. The employing of lithium complexes is also significant, because of the need to find cheap and green alternatives to noble metal complexes. (C) 2021 Elsevier B.V. All rights reserved.

Unsymmetrical sp(2)-sp(3) disilenes - Bisai, Milan Kumar; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2021)
Disilenes with differently coordinated silicon atoms are not known. Here, we have shown the high yield synthesis of a range of disilenes (2-4 and 6) upon reaction of a hypersilyl silylene PhC(NtBu)(2)SiSi(SiMe3)(3) (1) with aliphatic chlorophosphines. The most striking characteristic of these disilenes is the presence of two differently coordinated Si atoms (one is three-coordinated, the other four-coordinated). The analogous reaction with Ph2PCl did not afford the desired disilene, but, surprisingly, led to the first tetraphosphinosilane (8). DFT calculations were performed to understand the bonding in disilenes and differences in reactivity of the complexes.
Keywords: chlorophosphine; DFT; disilene; hypersilylsilylene

New record of larval-pupal endoparasitoid Exorista deligata parasitising Indian Tea looper Hyposidra talaca from India - Sharma, Pooja V.; Das, Tamal; Mukherjee, Susmita; Pathan, Ejaj K.; Rahman, Azizur; Gathalkar, Ganesh B. (Phytoparasitica, 2024)
This is the first record of Exorista deligata (Pandell & eacute;, 1896) (Diptera: Tachinidae) as a parasitoid of Hyposidra talaca (Walker, 1860) (Lepidoptera: Geometridae) from India. H. talaca is a major and new emerging defoliator of the Tea plant Camellia sinensis (L) Kuntze (Theaceae). It completes multiple generations per year without diapause on C. sinensis, resulting in heavy crop loss. The field-collected larvae/pupa of H. talaca were checked for parasitoid infestations and reared until either the host or parasitoid emerged. The parasitoid was identified as E. deligata with morphological characteristics and confirmed by the mitochondrial cytochrome oxidase subunit-I (COX-CO1) gene sequencing technique. The parasitoid is infrequent with unexplored parasitic biology. It parasitises the larva and completes its lifecycle inside the developing H. talaca by entirely devouring the host. The mean percent parasitisation caused by E. deligata studied herein was 25.4% (range 5.88%-57.69%). Based on its parasitisation ability, we suggest the species could be a potential biological control agent to address the damage mitigation caused by the tea looper pest, H. talaca.
Keywords: Biocontrol; Exorista deligata; Hyposidra talaca; Invasive pest; Parasitisation

Nickel-catalyzed tandem conversion of paraformaldehyde : methanol to hydrogen and formate/chemo- and stereoselective hydrogenation of alkynes under neutral conditions - Subaramanian, Murugan; Padhy, Subarna Sukanya; Gouda, Chandrakanth; Das, Tamal; Vanka, Kumar; Balaraman, Ekambaram (Catalysis Science and Technology, 2024)
The development of new catalytic protocols for clean and COx-free hydrogen generation from fundamental feedstocks is always interesting and challenging. Herein, we disclose nickel-catalyzed dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free and activator-free conditions. The dihydrogen generation from this redox combination under neutral, oxidative coupling conditions has been integrated with the hydrogen transfer reactions such as chemo- and stereoselective hydrogenation of alkynes in a tandem manner. This unprecedented strategy provides diverse highly stereoselective olefins with excellent tolerance of reducible functional groups such as ether, silyl ether, aldehyde, keto, ester, nitrile, halides including bromo and iodo groups, and heteroarenes. Additionally, we demonstrated catalytic stereo-interconversion of alkenes under benign conditions. The affordable gram-scale synthesis of some important pharmaceutical bioactive molecules has further enhanced their synthetic value. A tandem dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free conditions followed by semihydrogenation of alkynes is reported.

Unravelling the prebiotic origins of the simplest α-ketoacids in cometary ices: a computational investigation - Dash, Soumya Ranjan; Pandya, Rinu; Singh, Geetika; Sharma, Himanshu; Das, Tamal; Haldar, Hritwik; Hotha, Srinivas; Vanka, Kumar (CHEMICAL COMMUNICATIONS, 2024)
Keywords: GLYOXYLATE; Hydrocarbons; Metabolism; Precursors